Factors influencing the prescription of intensive combination treatment strategies for early rheumatoid arthritis. (August 2014) - Meyfroidt, S; van Hulst, L; De Cock, D; Van der Elst, K; Joly, J; Westhovens, R; Hulscher, M; Verschueren, P
<x xml:space="preserve">Abstract</x> Objectives: Despite the availability and demonstrated effectiveness of intensive combination treatment strategies (ICTS) for early rheumatoid arthritis (RA), a discrepancy seems to exist between theoretical evidence and actual prescription in daily practice. The purpose of this study was to explore and identify the factors influencing the prescription of ICTS. Method: This study involved rheumatologists and nurses participating in the Care for Rheumatoid Arthritis (CareRA) trial, a multicentre randomized controlled trial (RCT) comparing different ICTS for early RA with conventional disease-modifying anti-rheumatic drugs (DMARDs) plus step-down glucocorticoids (GCs). A qualitative study was carried out using individual semi-structured interviews. Each interview was recorded, transcribed literally, and analysed thematically. In addition, observations at outpatient clinics were used to clarify the interpretation of the results. Results: We interviewed 26 rheumatologists and six nurses and observed five outpatient visits. Identified facilitators included available scientific evidence, personal faith in treatment strategy, staff support, and low treatment costs. Rheumatologists had no doubts about the value of methotrexate (MTX) but some questioned the value of combination strategy, others the effectiveness and/or the dosage of individual compounds. Additional barriers for prescribing ICTS included need for patient education, fear for patients' preconceptions, concerns about applicability to the individual patient, difficulties with breaking routine, interference with organizational structures and processes, time constraints, and lack of financial support. Conclusions: A heterogeneous set of factors highlights the complexity of prescribing ICTS for early RA in daily clinical practice. Future improvement strategies should stimulate the facilitators while at the same time addressing the barriers. The generalizability of these findings to other health care systems needs further examination.